Suggested guidelines for conducting regional trials - Toro M., J.C. (International Center for Tropical Agriculture, 1978)
A complete set of guidelines is provided for conducting cassava regional trials. In addition to general guidelines on site selection, exptl. design, planting and harvesting time, and others, specific recommendations are given on technology to be used for the different agronomic practices required, data collection, disease and insect damage evaluations, trial methodology, and strategies for selecting promising var. (CIAT)